74.6k views
4 votes

\rm \int_( 0)^ {\large\frac{\pi}4} \sqrt{ \tan(x) - \tan {}^(2) (x) } \: dx \\

1 Answer

6 votes

First substitute
x=\tan^(-1)(y) to rewrite the integral as


\displaystyle \int_0^(\pi/4) √(\tan(x) - \tan^2(x)) \, dx = \int_0^1 (√(y-y^2))/(1+y^2) \, dy

Now use an Euler substitution,
z=\frac{√(y-y^2)}y to rewrite it again as


\displaystyle \int_0^(\pi/4) √(\tan(x) - \tan^2(x)) \, dx = 2 \int_0^\infty (t^2)/((t^2+1)^2 + 1) (t^2 + 1)) \, dt

where we take


√(y - y^2) = √(-y(y-1)) = yt \implies y = \frac1{1+t^2} \text{ and } dy = -(2t)/((1+t^2)^2) \, dt

Partial fractions:


\displaystyle (t^2)/(((t^2+1)^2+1) (t^2 + 1)) = (t^2+2)/(t^4+2t^2+2) - \frac1{t^2+1}

so that


\displaystyle \int_0^(\pi/4) √(\tan(x) - \tan^2(x)) \, dx = 2 \left(\int_0^\infty (t^2+2)/(t^4+2t^2+2) \, dt - \int_0^\infty (dt)/(t^2+1)\right)

The second integral is trivial,


\displaystyle \int_0^\infty (dt)/(t^2+1) = \lim_(t\to\infty)\tan^(-1)(t) - \tan^(-1)(0) = \frac\pi2

For the other, I'm compelled to use the residue theorem, though real methods are doable too (e.g. trig substitution). Consider the contour integral


\displaystyle \int_\Gamma f(z) \, dz = \int_\Gamma (z^2+2)/(z^4+2z^2+2) \, dz

where
\Gamma is a semicircle in the upper half of the complex plane, and its diameter lies on the real axis connecting
-R to
R. The value of this integral is 2πi times the sum of the residues in the upper half-plane. It's fairly straightforward to convince ourselves that the integral along the circular arc vanishes as
R\to\infty, so the contour integral converges to the integral over the entire real line. Note that


\displaystyle 2 \int_0^\infty (t^2+2)/(t^4+2t^2+2) \, dt = \int_(-\infty)^\infty (t^2+2)/(t^4+2t^2+2) \, dt

since the integrand is even.

Find the poles of
f(z).


z^4 + 2z^2 + 2 = 0 \\\\ ~~~~ \implies (z^2+1)^2 = -1 \\\\ ~~~~ \implies z^2 = -1 \pm i \\\\ ~~~~ \implies z = \pm √(-1 \pm i) = \sqrt[4]{2}\, e^(\pm i(3\pi/8 + \pi k))

where
k\in\{0,1\}.

The two poles we care about are at
z_1=\sqrt[4]{2}\,e^(i\,3\pi/8) and
z_2=\sqrt[4]{2}\,e^(-i\,11\pi/8). Compute the residues at each one.


\displaystyle \mathrm{Res}\left\{f(z),z=z_1\right\} = \lim_(z\to z_1) (f(z))/(z-z_1) = -\frac1{2^(7/4)}\,ie^(-i\,\pi/8) \\\\ ~~~~~~~~~~~~~~~~~~~~~~~~= -\frac1{2^(7/4)} \left(\sin\left(\frac\pi8\right) + i \cos\left(\frac\pi8\right)\right)


\displaystyle \mathrm{Res}\left\{f(z),z=z_2\right\} = \lim_(z\to z_2) (f(z))/(z-z_2) = -\frac1{2^(7/4)}\,ie^(i\,\pi/8) \\\\ ~~~~~~~~~~~~~~~~~~~~~~~~= \frac1{2^(7/4)} \left(\sin\left(\frac\pi8\right) - i \cos\left(\frac\pi8\right)\right)

By the residue theorem,


\displaystyle \int f(z) \, dz = 2\pi i \sum_(\rm poles) \mathrm{Res}\{f(z)\} = (4\pi)/(2^(7/4)) \cos\left(\frac\pi8\right)

We also have


\displaystyle \cos^2\left(\frac\pi8\right) = \frac{1 + \cos\left(\frac\pi4\right)}2 = \frac{2 + \sqrt2}4 \implies \cos\left(\frac\pi8\right) = \frac{√(2+\sqrt2)}2

Then the remaining integral is


\displaystyle \int_0^\infty (t^2+2)/(t^4+2t^2+2) \, dt = (4\pi)/(2^(7/4)) \cos\left(\frac\pi8\right) = \sqrt{\frac12 + \frac1{\sqrt2}} \, \pi

It follows that


\displaystyle \int_0^(\pi/4) √(\tan(x) - \tan^2(x)) \, dx = \boxed{\left(\sqrt{\frac12 + \frac1{\sqrt2}} - 1\right) \pi}

User Tejas Patil
by
5.5k points